11-Oxoaerothionin isolated from the marine sponge Aplysina fistularis shows anti-inflammatory activity in LPS-stimulated macrophages - Medeiros, Alexandra Ivo de [UNESP]; Gandolfi, Renata C.; Secatto, Adriana; Falcucci, Romulo M.; Faccioli, Lucia H.; Hajdu, Eduardo; Peixinho, Solange; Berlinck, Roberto G. S. (Informa Healthcare, 2012)
Marine sponges of the order Verongida are a rich source of biologically active bromotyrosine-derived secondary metabolites. However, none of these compounds are known to display anti-inflammatory activity. In the present investigation, we report the anti-inflammatory effects of 11-oxoaerothionin isolated from the Verongida sponge Aplysina fistularis. When RAW264.7 cells and primary macrophages were preincubated with 11-oxoaerothionin and stimulated with LPS (lipopolysaccharide), a concentration-dependent inhibition of iNOS (inducible nitric oxide synthase) protein and NO2- (Nitrite) production were observed. The same effect was observed when proinflammatory cytokines and PGE(2) (Prostaglandin E2) production was evaluated. In summary, we demonstrated that in the presence of LPS, 11-oxoaerothionin suppresses NO2 and iNOS expression as well as inflammatory cytokines and PGE(2).
Keywords: Prostaglandin E2; macrophages; inflammatory cytokines; nitric oxide; NF-kappa B and lipopolysaccharide